Gendered dimensions of environmental health, contaminants and global change in Nunavik, Canada - Kafarowski, Joanna (Études/Inuit/Studies, 2006)
AbstractAs has been well-documented in the scholarly literature over the last two decades, contaminants pose a potentially significant threat to the short and long-term health of Arctic human and natural environments and raise questions of social and environmental justice. Studies link contaminants such as heavy metals, persistent organic pollutants and radionuclides with the use of traditional country foods by Indigenous peoples including the Inuit. Adversely impacting Inuit communities in a myriad of ways, contaminants represent one manifestation of global change across the circumpolar North. Focusing on the community of Inukjuak, Nunavik (Northern Québec), Canada, this paper investigates the roles of Inuit women and men vis-à-vis participation in hunting activities and the identification of contaminants, and demonstrates how women and men construct the lead contaminant issue differently. Additionally, the paper explores why including the perspectives of both is critical to the development of effective environmental health policies, programs and strategies in response to these contaminants.